EFL LEARNING AS INDONESIAN-ENGLISH INTERCULTURAL LEARNING - Maulia, Bunga Putri (Jurnal Review Pendidikan dan Pengajaran, 2025)
This study explores English as a Foreign Language (EFL) learning within the framework of Indonesian-English intercultural learning. Through library research, the paper investigates the interconnection between language and culture, focusing on the perspectives of language, culture, and their roles in EFL learning contexts in Indonesia. The research addresses the significance of integrating both source culture (Indonesian) and target culture (English) in language education to develop students' intercultural awareness and competence. Findings highlight that effective EFL learning goes beyond grammatical competence to include cultural understanding, where learners become aware of both their own cultural identity and the target culture simultaneously. The study concludes that the balanced integration of source and target cultural elements in EFL classrooms enables learners to appreciate cultural differences, develop pride in their own culture, and become effective intercultural communicators. The paper offers suggestions for implementing intercultural awareness in Indonesian EFL settings, emphasizing the importance of creating meaningful learning activities that facilitate cultural exploration while developing English language skills.